Music in fundus disease: current applications and future prospects - PU Jiaxin; JI Yuying (Yanke Xuebao)
Music, as a non-invasive sensory stimulus, has been increasingly applied in medical fields due to its unique therapeutic value. This article reviews the current applications and research progress of music in fundus examination and treatment.Extensive clinical studies have demonstrated that music intervention can significantly reduce patients' anxiety levels during ophthalmic procedures and improve their medical experience. Positive effects have been observed across various clinical scenarios, including intravitreal injections, retinopathy of prematurity screening, and visual field examinations.Furthermore, studies on simulated ophthalmic surgical procedures have shown that background music not only does not interfere with surgeons' operational performance but may actually optimize the surgical environment by regulating the operator's psychological state. Although the effectiveness of music intervention varies among individuals, with patients showing different preferences for music types, rhythms, and volumes, music therapy generally demonstrates promising potential in fundus clinical practice as a safe, economical, and easily implemented auxiliary measure. Preliminary studies have demonstrated that music can reduce cell apoptosis and improve depression in rat models of diabetic retinopathy complicated with depression. Looking forward, more rigorous randomized controlled trials are needed to establish standardized music intervention protocols to maximize the positive effects of music in ophthalmic treatment.Meanwhile, emphasis should be placed on the principle of individualized treatment, developing appropriate music intervention strategies based on patients' personal preferences and specific clinical conditions.